RELIGIOUS BELIEFS AS A VISUAL IDEOLOGY OF THE EDITORIAL CARTOON OF KOMPAS NEWSPAPER IN SOCIOPOLITICAL CONTEXT OF INDONESIA - Sufriyanto Talani, Noval
Editorial cartoons are not just funny pictures that cause smiles and laughter, on the contrary, they have ideological content, contain emotional symbolic messages, and have the potential to spark controversy. Moreover, cartoons that reflect a religious belief. The controversy over the cartoon of the Prophet Muhammad published by Jyllands-Posten and Chalie Hebdo is a concrete example. Likewise, the cartoon published on the 26 February 2018 edition of Tempo Magazine has sparked controversy because it was considered to have insulted the figure of the Front Pembela Islam (FPI), Habib Riziek Shihab. These two examples illustrate how a cartoon has religious ideological content and creates emotional controversy. The facts above underlie this dissertation research conducted, namely to examining religious beliefs as the basis of editorial cartoon visual ideology. The editorial cartoons studied were the editorial cartoons published by the Kompas newspaper. The basic reason is that Kompas as one of the largest and oldest media in Indonesia has consistently published editorial cartoons since 1967, and was founded by a Catholic minority group. The background of its founders sparked the stereotype of Kompas as an acronym for “Komando Pastor”, a stereotype that indicates the role and influence of religion in the journalistic practice of the Kompas newspaper. The problems raised in this research are: (1) how does the sign system of the editorial cartoons in Kompas newspaper reflect religion belief? (2) Based on its sign system, how can the meaning and religious ideological content are conveyed rhetorically through the editorial cartoon of the Kompas newspaper? (3) What is the position of religious belief in ideological relation of editorial cartoon, Kompas newspaper and socio-political context in terms of the agenda and framing of media text publishing? Research objectives were (1) to find the form of Kompas newspaper editorial cartoons’ sign system that reflect a religious belief; (2) exploring the meaning of the editorial cartoon and religious ideological content that works through editorial cartoon sign system to find rhetorical form that is used by the Kompas cartoonist in the cartoons that reflect a religious belief; (3) To find a model regarding the position of religion in ideological relation between editorial cartoons, the Kompas iv newspaper and socio-political context of Indonesia as the cultural background covering the publication of the cartoons. This research uses qualitative method, combining Roland Barthes semiotic analysis tools with framing and content relation analysis. Data analysis is divided into three stages. The first and second stage use semiotic analysis to analyze Kompas newspaper editorial cartoon visual sign system to unveil the religious identity signs, denotative and connotative meaning, myth and its religious ideological content. The third stage uses analysis of content relation and framing to analyze the relation between text (news, news picture, editorial, editorial cartoon, opinion article) in order to reveal the position of religion in the ideological relations between editorial cartoon, the Kompas newspaper and the socio-political context of Indonesia. The results of the research found that (1) through the Kompas newspaper editorial cartoon visual sign system a situation setting was built in which there was an event situation and a comment situation. Visual signs that represent religious identity only appear in the setting of event, consisting of clothing and religious symbols. Religious identity in clothing such as Muslim clothing and Knights Templar armor in the Crusades. Meanwhile, the religious symbol is in the form of a Christmas tree and gestures for Catholic prayer, namely the Hail Mary. (2) From the meaning of the editorial cartoon, it is revealed that the ideological content of religion is dominated by Christian/Catholic religious beliefs. Irony, satire, humor, and metaphors are rhetorical forms that disguise the religious ideological content of its editorial cartoon, especially the ideology of anti-Islamic sharia (qishash law), anticorruption, humanism and anti-violence, anti-religion, and Christian/Catholic belief systems. (3) Contextually a strong relationship is formed between the editorial cartoon, Kompas newspaper, and the Indonesian socio-political context. The relationship is formed through the cartoon editorial publishing text setting agenda, news, news photos, editorials, and opinion articles. However, in terms of religious ideology, there are editorial cartoons that have relationship with other texts and some that have no relationship at all, either with texts published simultaneously or previously published texts. This research concludes that the Christian/Catholic religious belief system becomes the basis for the visual ideology of the editorial cartoon of the Kompas newspaper and the parallel principles of transcendental humanism. This ideology works behind the editorial cartoon visual sign system that is produced to comment on and respond to socio-political events that occur in Indonesia. Behind the socio-political criticism lies the mission of spreading the religious belief system which is carried out through editorial cartoons